Effectiveness Of Teacher And Student Communication In The Learning Process Through Quipper School At Private High School Of Pgri 12 Medan (International Journal of Cultural and Social Science, 2022)
This research was motivated by the fact that during the Covid-19 pandemic the learning system was shifted online, this was also in accordance with instructions from the government. With the aim of knowing the effectiveness of teacher and student communication during the learning process through Quipper School at SMA PGRI 12 Medan. The theory used in this study is the theory of Uses and Effects. The method used in this research is descriptive qualitative. With data collection techniques, namely interviews, observation and documentation. Then the results obtained from the study showed that teacher and student communication through Quipper School in the learning process was less effective because there were still students who did not understand or understand the learning material provided by the teacher, and there were several obstacles to teacher and student communication in the learning process through Quipper School. so that it can reduce the effectiveness of teacher and student communication in the learning process.